Microstructure and Tribological Properties of FeNPs@a-C:H Films by Micromorphology Analysis and Fractal Geometry - Ţălu, Ştefan; Bramowicz, Miroslaw; Kulesza, Slawomir; Shafiekhani, Azizollah; Ghaderi, Atefeh; Mashayekhi, Fatemeh; Solaymani, Shahram (Industrial & engineering chemistry research, 2015)
This paper analyzes the three-dimensional (3D) surface texture of amorphous hydrogenated carbon films with sputtered iron nanoparticles (FeNPs@a-C:H) deposited by a radio-frequency plasma-enhanced chemical vapor deposition method on the quartz substrates. The prepared FeNPs@a-C:H films were used as research materials. The synthesized samples were deposited at four different pressures of 2.5, 3, 3.35, and 3.5 N/m2 in an acetylene gas atmosphere. The Fe and C contents of the thin films were obtained from X-ray photoelectron spectroscopy. The X-ray diffraction profile and electron diffraction pattern indicate that iron nanoparticles with body-centered-cubic crystalline structure are formed in these films. The localized surface plasmon resonance peak that is the signature of the existence of the iron core nanoparticles appears in visible spectra of these films. The sample surface images were recorded using an atomic force microscope operating in a noncontact mode and analyzed to reveal the statistical, fractal, and functional surface properties of prepared samples. Analysis of the 3D surface texture is essential for the correct interpretation of surface topographic features as well as its functional role for the test surface. It also helps to understand the relationship between the surface topography and functional properties.